Initiation of petn explosive decomposition by CO2 laser; Известия вузов. Физика; Т. 55, № 11-3 - Razin A. V. Aleksey Valerievich; Tsipilev V. P. Vladimir Papilovich; Yakovlev A. N. Aleksey Nikolaevich; Damamme G. R.; Malys D. (2012, 2012)
Заглавие с экрана